(3cfR GdYQaGf aj abg GdbQBfs - (3GdSjhQj, GdMdj, GdCSOj, CHh YHO Gddg, TQa GdOjf, ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826s
(3ChdgG (B:s
(3GdMeO ddg (B... (3aMOGfj Pdc Edi hVY cJGH jTJed Ydi ahGFO NdG YfgG CcKQ GdJaGSjQ haQGFO de jba YdjgG EdG cd fMQjQ hVeeJ Edi Pdc aQhYG abgjI JbJVjgG fUhU Jdc GdBjGJ Ch XhGgQgG (B...s
(3BNQgG (B:s
... (3KGfjG hbhd (B.. (3Cj GdYOd CbQH ddJbhi Cj EdjgG haj Pdc eHGdZI YXjeI aj GdYOd MjK LYd CbQH MUhd eagheG gP haj GdBjI CjVG JCcjO ddCeQ HEbGeI GdTgGOI (B.. (3MGeOjf ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\282s
(3GdPQjYI (B18 \ 1184s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs